Weather-resistant exposed coating composite waterproof coiled material and preparation method thereof

By using a composite layer of modified asphalt layer and fiberglass cloth exposed coating in the waterproof roll, combined with a reinforcement layer and an isolation layer, the defects of the existing waterproof roll in terms of weather resistance, flame retardant performance and ultraviolet resistance are solved, and efficient waterproof performance and long-term use stability are achieved.

CN118580783BActive Publication Date: 2025-03-28NANTONG KESHUN NEW BUILDING MATERIALS CO LTD +1
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202410730578.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-06-06
Publication Date
2025-03-28
Estimated Expiration
2044-06-06

AI Technical Summary

Technical Problem

The existing waterproof coils have defects in weather resistance, flame retardant properties and UV resistance during long-term exposure, resulting in a shortened service life and a reduced waterproof effect.

Method used

An exposed coating composite layer formed by a modified asphalt layer and a glass fiber cloth with specific performance parameters is combined with a reinforcement layer and an optional isolation layer to form a weather-resistant exposed coating composite waterproof coil. The modified materials contain bitumen, polyaluminum chloride, cycloane oil, SBS, SBR, tris(2,3-dichloropropyl) phosphate, SIS, 3-methyltetrahydrothiazole-2-thioone, gumalon resin and aluminum hydroxide.

Benefits of technology

It realizes the waterproof coil resistance to ultraviolet aging, excellent weather resistance, good viscosity, strong flame retardant and tensile performance of the waterproof coil, and is easy to construct and firmly bonded to the base surface.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004880095560000121
    Figure BDA0004880095560000121
  • Figure BDA0004880095560000141
    Figure BDA0004880095560000141
  • Figure BDA0004880095560000151
    Figure BDA0004880095560000151
Patent Text Reader

Abstract

The present invention relates to the technical field of waterproofing coiled materials, and discloses a weather-resistant exposed coating composite waterproofing coiled material and a preparation method thereof. The waterproofing coiled material comprises a modified asphalt layer, an exposed coating composite layer, and a reinforcement layer which are sequentially stacked; the exposed coating composite layer contains a glass fiber cloth and a weather-resistant acrylic coating arranged on one side surface of the glass fiber cloth; the glass fiber cloth has a tensile breaking strength of 1500-2300N / 2.5cm and a gram weight of 450-850g / m 2 The waterproof roll material provided by the present invention can resist ultraviolet aging and has excellent weather resistance; it has strong adhesiveness, good tensile properties, and strong flame retardant properties; at the same time, it can be firmly bonded to the base surface and has high safety.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of waterproof coiled materials, and in particular to a weather-resistant exposed coating composite waterproof coiled material and a preparation method thereof. Background Art

[0002] The current waterproof membrane is mainly asphalt waterproof membrane, including a base made of materials such as polyester felt, glass fiber felt or glass fiber reinforced polyester felt, an asphalt layer dipped on the surface of the base, and isolation material layers on the upper and lower surfaces.

[0003] Asphalt waterproofing membranes have poor high temperature resistance during use. After hot and cold cycles, their performance deteriorates. In addition, when used on roofs, they are exposed to sunlight for a long time, which causes photochemical reactions, thus reducing their service life. Generally, they need to be replaced after a few years of use. Changes in the components of the asphalt layer will greatly affect the performance of the waterproofing membrane, such as heat resistance, low temperature flexibility, impermeability, and tensile strength.

[0004] The existing construction of modified asphalt waterproofing membranes is mainly non-exposed, and some exposed products have poor weather resistance. The main materials on the surface of currently exposed asphalt-based membranes are fine sand or weather-resistant composite membranes.

[0005] CN105398103A discloses an SBS modified asphalt waterproofing roll with a reinforcement layer, which is a layered structure, and the upper non-woven reinforcement layer and the lower non-woven reinforcement layer are made of polyester fiber, glass fiber and carbon fiber interlaced and pressed. The waterproofing roll has good heat resistance, low-temperature flexibility and tensile strength, but it is still difficult to resist in some harsh environments. For example, under the influence of cold air in the north, the temperature may be below minus 30°C, and the roll is easy to crack. In places near heat treatment equipment such as boilers, the local ambient temperature may be higher than 100°C. Since most of the materials of the waterproofing roll are organic materials, they are flammable and are easy to cause fires under certain circumstances.

[0006] CN109878190A discloses a method for preparing a thermoplastic polyurethane modified asphalt waterproofing membrane, in which bistrifluoromethanesulfonyl imide is introduced into the modified asphalt through cross-linking with isocyanate, so that the aging resistance of the modified asphalt is enhanced. However, long-term exposure of the waterproofing membrane will lead to a decrease in ultraviolet resistance and the phenomenon of film separation, which will seriously affect the waterproofing effect. Summary of the invention

[0007] The purpose of the present invention is to overcome the defects of the waterproof roll material provided by the prior art, such as weak weather resistance, poor flame retardancy and decreased UV resistance when exposed to the outside for a long time.

[0008] The inventors of the present invention have found in the course of research that when the modified asphalt layer provided by the present invention is used in conjunction with an exposed coating composite layer formed by glass fiber cloth or the like with specific performance parameter characteristics, the formed weather-resistant exposed coating composite waterproofing coiled material can resist ultraviolet aging and has excellent weathering effect. When the waterproofing coiled material is exposed for a long time, the modified asphalt layer does not delaminate from its upper surface, has good stickiness, and has strong flame retardant and tensile properties. In view of this, the present invention provides the following technical solutions.

[0009] In order to achieve the above-mentioned object, the first aspect of the present invention provides a weather-resistant exposed coating composite waterproofing roll material, the waterproofing roll material comprises a modified asphalt layer, an exposed coating composite layer, and a reinforcement layer stacked in sequence; optionally, the waterproofing roll material further comprises an isolation layer arranged on the surface of the modified asphalt layer; wherein,

[0010] Based on the total weight of the modified material forming the modified asphalt layer, the modified material contains: 40-55wt% of asphalt, 0.5-2wt% of polyaluminium chloride, 5-10wt% of cyclohexane oil, 2-8wt% of SBS, 2-6wt% of SBR, 0.5-3wt% of tris(2,3-dichloropropyl) phosphate, 2-6wt% of SIS, 0.05-1wt% of 3-methylthiazolidine-2-thione, 8-15wt% of coumarone resin, and 20-30wt% of aluminium hydroxide;

[0011] The exposed coating composite layer contains glass fiber cloth and a weather-resistant acrylic coating arranged on one side of the glass fiber cloth; the tensile breaking strength of the glass fiber cloth is 1500-2300N / 2.5cm, and the gram weight is 450-850g / m 2 .

[0012] The second aspect of the present invention provides a method for preparing the weather-resistant exposed coating composite waterproof membrane according to the first aspect, the method comprising the following steps:

[0013] (1) applying a weather-resistant acrylic coating to one side of a glass fiber cloth to obtain an exposed coating composite layer containing a weather-resistant acrylic coating; the glass fiber cloth has a tensile breaking strength of 1500-2300 N / 2.5 cm and a gram weight of 450-850 g / m 2 ;

[0014] (2) applying the material I forming the reinforcement layer to the surface of the weather-resistant acrylic coating of the exposed coating composite layer to obtain an intermediate I;

[0015] (3) coating the modified material for forming the modified asphalt layer on the surface of the exposed coating composite layer of the intermediate I, and performing a molding process to obtain a molding material I containing the modified asphalt layer;

[0016] Optionally, the method further comprises: bonding an isolation layer to the surface of the modified asphalt layer of the molding material I;

[0017] In step (3), based on the total weight of the modified material, the modified material contains: 40-55wt% of asphalt, 0.5-2wt% of polyaluminium chloride, 5-10wt% of cyclohexane oil, 2-8wt% of SBS, 2-6wt% of SBR, 0.5-3wt% of tris(2,3-dichloropropyl) phosphate, 2-6wt% of SIS, 0.05-1wt% of 3-methylthiazolidine-2-thione, 8-15wt% of coumarone resin, and 20-30wt% of aluminium hydroxide.

[0018] The above technical solution of the present invention has at least the following advantages over the prior art:

[0019] (1) The waterproof roll provided by the present invention is resistant to ultraviolet aging and has excellent weather resistance. It remains unchanged after being exposed for three years after construction. Moreover, when the waterproof roll is exposed for a long time, the modified asphalt layer does not delaminate from its upper surface and has good adhesion.

[0020] (2) The waterproof roll material provided by the present invention has good tensile properties and strong flame retardant properties; at the same time, it is easy to construct during use, and the construction method can be wet laying or dry laying. It can be constructed on a cement base surface or a color steel tile roof, and can be firmly bonded to the base surface, with high safety.

[0021] (3) In the preparation method of the weather-resistant exposed coating composite waterproof roll provided by the present invention, the reaction conditions are mild and controllable, less irritating gas is generated, and the entire preparation process is green and environmentally friendly. DETAILED DESCRIPTION

[0022] The endpoints and any values ​​of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.

[0023] As mentioned above, the first aspect of the present invention provides a weather-resistant exposed coating composite waterproofing roll, the waterproofing roll comprises a modified asphalt layer, an exposed coating composite layer, and a reinforcement layer stacked in sequence; optionally, the waterproofing roll also comprises an isolation layer arranged on the surface of the modified asphalt layer; wherein,

[0024] Based on the total weight of the modified material forming the modified asphalt layer, the modified material contains: 40-55wt% of asphalt, 0.5-2wt% of polyaluminium chloride, 5-10wt% of cyclohexane oil, 2-8wt% of SBS, 2-6wt% of SBR, 0.5-3wt% of tris(2,3-dichloropropyl) phosphate, 2-6wt% of SIS, 0.05-1wt% of 3-methylthiazolidine-2-thione, 8-15wt% of coumarone resin, and 20-30wt% of aluminium hydroxide;

[0025] The exposed coating composite layer contains glass fiber cloth and a weather-resistant acrylic coating arranged on one side of the glass fiber cloth; the tensile breaking strength of the glass fiber cloth is 1500-2300N / 2.5cm, and the gram weight is 450-850g / m 2 .

[0026] Preferably, in the modified material, the asphalt is 90# asphalt, and the softening point of the 90# asphalt is ≥46°C.

[0027] Preferably, in the modified material, the basicity of the polyaluminium chloride is 45-80%. The inventors of the present invention have found that under this preferred condition, the waterproofing coiled material provided by the present invention has better high temperature resistance.

[0028] The present invention has no special requirements on the specific types of the cyclohexane oil and coumarone resin. The following text of the present invention provides specific types of cyclohexane oil and coumarone resin as examples, which should not be understood by those skilled in the art as limiting the present invention.

[0029] The SBS described in the present invention represents a styrene-butadiene-styrene triblock copolymer.

[0030] Preferably, in the modified material, based on the total weight of the SBS, the content of the styrene structural unit in the SBS is 25-34wt%, the content of the butadiene structural unit is 66-75wt%, and the number average molecular weight of the SBS is 100,000-150,000. The inventors of the present invention have found that in this preferred case, the waterproof roll material provided by the present invention has better durability.

[0031] According to a particularly preferred embodiment, the SBS is a star-type SBS.

[0032] The SBR described in the present invention refers to styrene-butadiene rubber.

[0033] Preferably, in the modified material, based on the total weight of the SBR, the styrene content in the SBR is 20-30wt%, the oil content is 20-35wt%, the raw rubber Mooney viscosity is 45-54 / ML(1+4)100°C, the 300% elongation stress is 9-10MPa (145°C, 35min), and the tensile strength is ≥20MPa (145°C, 35min).

[0034] The SIS described in the present invention represents a styrene-isoprene-styrene triblock copolymer.

[0035] In the modified material, based on the total weight of the SIS, the content of the styrene structural unit in the SIS is 10-20wt%, and the content of the isoprene structural unit is 80-90wt%.

[0036] Preferably, in the exposed coating composite layer, the sodium oxide content in the glass fiber cloth is ≤1wt%.

[0037] The present invention has no particular limitation on the average thickness of the glass fiber cloth, and those skilled in the art can select it as needed. For example, the average thickness of the glass fiber cloth can be 0.2-0.8 mm.

[0038] Preferably, in the exposed coating composite layer, the sodium oxide content in the glass fiber cloth is ≤1wt%. The inventors of the present invention have found that in this preferred case, the waterproof coiled material provided by the present invention has better weather resistance.

[0039] Preferably, in the exposed coating composite layer, the weather-resistant acrylic coating is formed by a weather-resistant acrylic coating, and based on the total weight of the weather-resistant acrylic coating, the weather-resistant acrylic coating contains: 25-35wt% of a weather-resistant acrylic emulsion, 24-40wt% of water, 0.01-0.5wt% of cellulose ether, 25-35wt% of talc, and 1-6wt% of titanium dioxide. In this preferred case, the waterproof roll provided by the present invention can achieve the effect of preventing the modified asphalt layer from delaminating from its upper surface, and at the same time has good resistance to ultraviolet aging.

[0040] Preferably, based on the total weight of the weather-resistant acrylic coating, the weather-resistant acrylic coating further contains 1-2.2 wt % of an additive combination, wherein the additive combination is a dispersant (9830A), a wetting agent (U-99), a pH regulator (APM-95) and a silicone defoamer (THIX-278).

[0041] Preferably, based on the total weight of the weather-resistant acrylic coating, the weather-resistant acrylic coating further contains 0.5-0.8wt% of a dispersant (9830A), 0.5-0.8wt% of a wetting agent (U-99), 0.1-0.3wt% of a pH regulator (APM-95) and 0.2-0.4wt% of a silicone defoamer (THIX-278).

[0042] Preferably, the viscosity of the weather-resistant acrylic coating at 23° C. is 500-2000 mPa.s.

[0043] The present invention has no special requirements for the specific preparation process of the weather-resistant acrylic coating. Those skilled in the art can prepare the coating by using a method known in the art, as long as the formula of the obtained weather-resistant acrylic coating meets the requirements of the present invention, for example, the raw material components of corresponding amounts can be added in sequence and stirred to obtain the weather-resistant acrylic coating. The present invention will not be described in detail here, and those skilled in the art should not be construed as limiting the present invention.

[0044] It should be noted that the aforementioned “25-35 wt % of weather-resistant acrylic emulsion” in the present invention refers to the proportion of the total weight of the weather-resistant acrylic emulsion (including the solute and solvent therein) in the weather-resistant acrylic coating.

[0045] Preferably, in the exposed coating composite layer, the content of the weather-resistant acrylic coating is 100-300 g relative to a square meter of the glass fiber cloth.

[0046] Preferably, the weight average diameter of the talc is 0.01 mm.

[0047] Preferably, the weight average diameter of the titanium dioxide is 0.01 mm.

[0048] Preferably, the reinforcement layer is formed by reaction sand with a weight average diameter of 0.25-0.7 mm. In this preferred case, the waterproof roll provided by the present invention has significantly stronger adhesion, and its modified asphalt layer does not delaminate from its upper surface.

[0049] Preferably, the isolation layer is a PET silicone oil film and / or a PE silicone oil film. The "PET" is polyethylene terephthalate; the "PE" is polyethylene.

[0050] Preferably, the average thickness of the isolation layer is 0.01-0.05 mm.

[0051] Preferably, the thickness ratio of the modified asphalt layer, the exposed coating composite layer and the reinforcement layer is 1:0.25-0.5:0.2-0.4.

[0052] As mentioned above, the second aspect of the present invention provides a method for preparing the weather-resistant exposed coating composite waterproof membrane according to the first aspect, the method comprising the following steps:

[0053] (1) applying a weather-resistant acrylic coating to one side of a glass fiber cloth to obtain an exposed coating composite layer containing a weather-resistant acrylic coating; the glass fiber cloth has a tensile breaking strength of 1500-2300 N / 2.5 cm and a gram weight of 450-850 g / m 2 ;

[0054] (2) applying the material I forming the reinforcement layer to the surface of the weather-resistant acrylic coating of the exposed coating composite layer to obtain an intermediate I;

[0055] (3) coating the modified material for forming the modified asphalt layer on the surface of the exposed coating composite layer of the intermediate I, and performing a molding process to obtain a molding material I containing the modified asphalt layer;

[0056] Optionally, the method further comprises: bonding an isolation layer to the surface of the modified asphalt layer of the molding material I;

[0057] In step (3), based on the total weight of the modified material, the modified material contains: 40-55wt% of asphalt, 0.5-2wt% of polyaluminium chloride, 5-10wt% of cyclohexane oil, 2-8wt% of SBS, 2-6wt% of SBR, 0.5-3wt% of tris(2,3-dichloropropyl) phosphate, 2-6wt% of SIS, 0.05-1wt% of 3-methylthiazolidine-2-thione, 8-15wt% of coumarone resin, and 20-30wt% of aluminium hydroxide.

[0058] Preferably, in step (1), based on the area of ​​the glass fiber cloth, the coating density of the weather-resistant acrylic paint is 100-300 g / m 2 .

[0059] Preferably, in step (2), based on the area of ​​the glass fiber cloth, the coating density of the material I of the reinforcement layer is 400-600 g / m 2 .

[0060] Preferably, in step (3), the coating thickness of the modified material is controlled so that the thickness ratio of the modified asphalt layer to the intermediate I is 1:0.5-0.9.

[0061] According to a preferred specific implementation, in step (1), the method further comprises: first subjecting the glass fiber cloth coated with the weather-resistant acrylic paint to a drying treatment I to obtain the exposed paint composite layer.

[0062] According to another preferred embodiment, in step (2), the method further comprises: first subjecting the exposed coating composite layer coated with the material I to a drying treatment II to obtain the intermediate I.

[0063] The present invention has no special requirements for the drying process I and the specific drying conditions of the drying process II, and those skilled in the art can perform the drying process according to conventional drying parameters in the art. For example, the temperature of the drying process I is 140-180°C and the time is 20-60 minutes; the temperature of the drying process II is 40-80°C and the time is 10-60 minutes.

[0064] It should be noted that in step (3), the surface of the exposed coating composite layer refers to the surface of the glass fiber cloth of the exposed coating composite layer.

[0065] Preferably, in step (3), the molding step includes: subjecting the intermediate I coated with the modified material to a constant thickness extrusion process.

[0066] According to a preferred specific implementation, the intermediate I is subjected to the thickness-fixing extrusion treatment using a thickness-fixing roller.

[0067] More preferably, the extrusion speed of the thickness setting roller is 15-30 m / min.

[0068] Preferably, after performing step (3), the isolation layer is bonded to the surface of the modified asphalt layer of the molding material I, and the obtained material is cooled so that the temperature of the obtained material is 0-40°C.

[0069] Preferably, the method further comprises: before carrying out the step (3), first preparing the modified material by a method comprising the following steps:

[0070] S1: in the presence of an organic solvent, subjecting the asphalt, the polyaluminium chloride and the naphthenic oil to a first reaction to obtain a first product;

[0071] S2: subjecting the first product to a second reaction with the SBS to obtain a second product;

[0072] S3: performing a third reaction on the second product, the SBR, the tris(2,3-dichloropropyl) phosphate and the SIS to obtain a third product;

[0073] S4: performing a fourth reaction on the third product, the 3-methylthiazolidine-2-thione and the coumarone resin to obtain a fourth product;

[0074] S5: performing a fifth reaction on the fourth product and the aluminum hydroxide to obtain the modified material;

[0075] The reaction conditions of the first reaction, the second reaction, the third reaction, the fourth reaction and the fifth reaction are independently as follows: the reaction temperature is 160-185°C and the reaction time is 60-130min. The inventors found that in this preferred case, the method for preparing the waterproof coiled material provided by the present invention produces less irritating gas and has a significant green environmental protection effect.

[0076] Preferably, the organic solvent is at least one of methyl pyrrolidone, dipropylene glycol methyl ether and ethylene glycol.

[0077] According to a preferred specific embodiment, in S1, the operation of subjecting the asphalt, the polyaluminium chloride and the cyclohexane oil to a first reaction in the presence of an organic solvent comprises: dissolving the polyaluminium chloride in the organic solvent to form a polyaluminium chloride solution, and then mixing the polyaluminium chloride solution with the asphalt and the cyclohexane oil to carry out the first reaction.

[0078] Preferably, the mass ratio of the polyaluminium chloride to the organic solvent is 1:1-5.

[0079] According to a particularly preferred embodiment, the conditions of the first reaction include: a reaction temperature of 160-185°C and a reaction time of 80-130min; the conditions of the second reaction include: a reaction temperature of 170-180°C and a reaction time of 80-120min; the conditions of the third reaction include: a reaction temperature of 160-180°C and a reaction time of 60-120min; the conditions of the fourth reaction include: a reaction temperature of 175-185°C and a reaction time of 100-120min; the conditions of the fifth reaction include: a reaction temperature of 170-180°C and a reaction time of 80-120min. In this preferred embodiment, the method for preparing a waterproof coiled material provided by the present invention generates less irritating gas and has a significant green environmental protection effect.

[0080] The present invention will be described in detail below by way of examples.

[0081] In the following examples, unless otherwise specified, the instruments, reagents, materials, etc. involved are all conventional instruments, reagents, materials, etc., which can be obtained through regular commercial channels. In particular, unless otherwise specified, the reagents used are all commercially available analytically pure products.

[0082] PET silicone oil film II was purchased from Shanghai Youpers Material Technology Co., Ltd.; the average thickness was 0.05 mm.

[0083] 90# asphalt, purchased from Sinopec Maoming Petrochemical Co., Ltd., brand 90 road asphalt, has a softening point of 46°C.

[0084] 70# asphalt, purchased from Sinopec Maoming Petrochemical Co., Ltd., brand 70 road asphalt, has a softening point of 48°C.

[0085] Polyaluminium chloride I was purchased from Gongyi Fuda Water Purification Materials Co., Ltd., brand yellow polyaluminium chloride; the basicity of polyaluminium chloride was 60%.

[0086] Polyaluminium chloride II was purchased from Zibo Wanzun Environmental Protection Materials Co., Ltd., and its brand is industrial grade polyaluminium chloride; the basicity of polyaluminium chloride is 40%.

[0087] Naphthenic oil was purchased from Shandong Taichang Petrochemical Technology Co., Ltd., brand name Naphthenic oil.

[0088] SBS was purchased from Ningbo Jinhai Chenguang Chemical Co., Ltd. with the brand name JH-7302. Based on the total weight of SBS, the content of styrene structural units in SBS was 30 wt%, and the content of butadiene structural units was 70 wt%. The number average molecular weight of SBS was 120,000.

[0089] SBR was purchased from Hangzhou Yibang Rubber Co., Ltd., brand 1712; based on the total weight of SBR, the styrene content in SBR was 23.4wt%; the oil content was 27.1wt%, the raw rubber Mooney viscosity was 50 / ML(1+4)100°C, the 300% elongation stress was 9.3MPa (145°C, 35min), and the tensile strength was 20.9MPa (145°C, 35min).

[0090] SIS was purchased from Baling Branch of China Petrochemical Corporation with a brand number of 1126. Based on the total weight of SIS, the content of styrene structural units in SIS was 16 wt %, and the content of isoprene structural units was 84 wt %.

[0091] Coumarone resin was purchased from Hengshui Zehao Rubber Chemical Co., Ltd., brand number 16#.

[0092] Glass fiber cloth I, purchased from Wanqing Chemical Technology Co., Ltd., brand EWR800; tensile breaking strength is 2300N / 2.5cm, gram weight is 800g / m 2 , wherein the sodium oxide content is 0.7wt%.

[0093] Glass fiber cloth II, purchased from Wanqing Chemical Technology Co., Ltd., brand EWR600; tensile breaking strength is 1900N / 2.5cm, gram weight is 600g / m 2 , wherein the sodium oxide content is 0.65wt%.

[0094] Glass fiber cloth III, purchased from Wanqing Chemical Technology Co., Ltd., brand EWR400; tensile breaking strength is 1400N / 2.5cm, gram weight is 400g / m 2 , wherein the sodium oxide content is 0.65wt%.

[0095] Weather Resistant Acrylic Paint

[0096] Weather-resistant acrylic emulsion was purchased from Shanghai Baolijia Chemical Co., Ltd. with the brand name BLJ-5619.

[0097] Cellulose ether was purchased from Hebei Shuangniu Building Materials Cellulose Co., Ltd., brand name hydroxymethyl cellulose 12000.

[0098] Talc powder was purchased from Pingdu Tianyi Powder Co., Ltd., with a weight average diameter of 0.01 mm.

[0099] Titanium dioxide was purchased from Hebei Weicai Pigment Co., Ltd., with a weight average diameter of 0.01 mm.

[0100] Additive Combination

[0101] 9830A, purchased from Guangzhou Kaiju Chemical Co., Ltd.

[0102] U-99 was purchased from Guangzhou Jinshengji Chemical Co., Ltd.

[0103] APM-95 was purchased from Weifang Kunlian Chemical Co., Ltd.

[0104] THIX-278 was purchased from Yantai Hengxin Chemical Technology Co., Ltd.

[0105] Reinforcement layer

[0106] Reaction sand was purchased from Lingshou County Wanzhu Mineral Products Co., Ltd., brand Mullite sand; the weight average diameter was 0.6 mm.

[0107] Isolation layer

[0108] PET silicone oil film I was purchased from Shanghai Youpers Material Technology Co., Ltd.; the average thickness was 0.03 mm.

[0109] In the following examples, based on the total weight of the weather-resistant acrylic coating, the weather-resistant acrylic coating contains 1.97 wt% of an additive combination, which is 0.7 wt% of 9830A, 0.7 wt% of U-99, 0.26 wt% of APM-95 and 0.31 wt% of THIX-278.

[0110] In the following examples, the area of ​​the glass fiber cloth used is the same, all 1m2 .

[0111] Preparation Example 1: Preparation of modified materials

[0112] S1: In the presence of 30 g of an organic solvent (methyl pyrrolidone), 900 g of asphalt, polyaluminium chloride and naphthenic oil are subjected to a first reaction to obtain a first product;

[0113] S2: subjecting the first product to a second reaction with SBS to obtain a second product;

[0114] S3: performing a third reaction on the second product with SBR, tris(2,3-dichloropropyl) phosphate and SIS to obtain a third product;

[0115] S4: subjecting the third product to a fourth reaction with 3-methylthiazolidine-2-thione and coumarone resin to obtain a fourth product;

[0116] S5: subjecting the fourth product to a fifth reaction with aluminum hydroxide to obtain a modified material (the weight of the modified material is 2073.7 g).

[0117] The preparation methods of different modified materials used in the examples of the present invention are the same, except that the formulas of the raw materials are different. The raw material formulas of different modified materials are listed in Table 1, and the unlisted parts are the same as those in Preparation Example 1.

[0118] Table 1

[0119]

[0120]

[0121] Example 1

[0122] (1) coating a weather-resistant acrylic coating on one side of the glass fiber cloth, and obtaining an exposed coating composite layer containing a weather-resistant acrylic coating after drying; the formula of the weather-resistant acrylic coating is listed in Table 2 (the weight of the weather-resistant acrylic coating is 300 g); the amount of the weather-resistant acrylic coating used per square meter of the glass fiber cloth is 300 g;

[0123] (2) applying a material I forming a reinforcement layer to the surface of the weather-resistant acrylic coating of the exposed coating composite layer to obtain an intermediate I; the material I is reaction sand;

[0124] (3) coating the modified material for forming the modified asphalt layer on the surface of the exposed coating composite layer of the intermediate I, and extruding the intermediate I to a certain thickness using a thickness roller at an extrusion speed of 25 m / min to perform a molding process to obtain a molding material I containing a modified asphalt layer;

[0125] (4) bonding the isolation layer (i.e., PET silicone oil film I) to the surface of the modified asphalt layer of the molding material I, and cooling the obtained material to a temperature of 40° C. to obtain a waterproof roll material.

[0126] The thickness ratio of the modified asphalt layer, the exposed coating composite layer and the reinforcement layer is 1:0.36:0.36.

[0127] The specific process parameters of this embodiment are shown in Table 3 and Table 4.

[0128] The remaining embodiments were carried out using the same process flow as that of Embodiment 1, except that the materials and process parameters were different, as shown in Tables 3 and 4.

[0129] Comparative Example 3

[0130] This comparative example is carried out in the same manner as in Example 1, except that in this comparative example, when preparing the exposed coating composite layer, an equal area of ​​PET silicone oil film II is used to replace the glass fiber cloth used in Example 1, and the rest is the same as in Example 1.

[0131] Table 2

[0132]

[0133] Table 3

[0134] Weather Resistant Acrylic Paint Fiberglass cloth types Modified materials Example 1 T1 Fiberglass cloth I G1 Example 2 T2 Fiberglass cloth II G1 Example 3 T1 Fiberglass cloth II G2 Example 4 T3 Fiberglass cloth I G1 Example 5 T1 Fiberglass cloth I G3 Example 6 T1 Fiberglass cloth I G4 Comparative Example 1 T1 Glass fiber cloth III G1 Comparative Example 2 T1 Fiberglass cloth I DG1

[0135] Table 4

[0136] Example 1 Example 2 Example 3 Example 4 Example 5 Example 6 First Response Reaction temperature / ℃ 185 Same as Example 1 160 Same as Example 1 Same as Example 1 Same as Example 1 Reaction time / min 120 Same as Example 1 90 Same as Example 1 Same as Example 1 Same as Example 1 Second reaction Reaction temperature / ℃ 180 170 Same as Example 1 Same as Example 1 Same as Example 1 Same as Example 1 Reaction time / min 100 80 Same as Example 1 Same as Example 1 Same as Example 1 Same as Example 1 The third reaction Reaction temperature / ℃ 180 165 178 Same as Example 1 Same as Example 1 Same as Example 1 Reaction time / min 110 70 115 Same as Example 1 Same as Example 1 Same as Example 1 Fourth reaction Reaction temperature / ℃ 180 178 180 Same as Example 1 Same as Example 1 Same as Example 1 Reaction time / min 100 110 115 Same as Example 1 Same as Example 1 Same as Example 1 The fifth reaction Reaction temperature / ℃ 175 170 172 Same as Example 1 Same as Example 1 Same as Example 1 Reaction time / min 100 115 90 Same as Example 1 Same as Example 1 Same as Example 1

[0137] Test Case

[0138] The performance of the waterproof membrane prepared in the example was tested using the test methods specified in "Wet-laid Waterproof Membrane" (GB / T 35467-2017), "Classification of Burning Performance of Building Materials and Products" (GB8624-2012) and "General Specification for Waterproofing of Buildings and Municipal Engineering" (GB 55030-2022). The specific results are shown in Table 5.

[0139] Table 5

[0140]

[0141] It can be seen from the results in Table 5 that the weather-resistant exposed coating composite waterproof membrane provided by the present invention is resistant to ultraviolet aging and has excellent weather resistance; it has strong adhesion, good tensile properties, and strong flame retardant properties; at the same time, it can be firmly bonded to the base surface and has high safety.

[0142] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.

Claims

1. A weather-resistant exposed coating composite waterproof coiled material, characterized in that: The waterproof roll material comprises a modified asphalt layer, an exposed coating composite layer, and a reinforcement layer which are stacked in sequence; optionally, the waterproof roll material further comprises an isolation layer arranged on the surface of the modified asphalt layer; wherein, Based on the total weight of the modified material forming the modified asphalt layer, the modified material contains: 40-55wt% of asphalt, 0.5-2wt% of polyaluminium chloride, 5-10wt% of cyclohexane oil, 2-8wt% of SBS, 2-6wt% of SBR, 0.5-3wt% of tris(2,3-dichloropropyl) phosphate, 2-6wt% of SIS, 0.05-1wt% of 3-methylthiazolidine-2-thione, 8-15wt% of coumarone resin, and 20-30wt% of aluminium hydroxide; The exposed coating composite layer contains glass fiber cloth and a weather-resistant acrylic coating arranged on one side of the glass fiber cloth; the tensile breaking strength of the glass fiber cloth is 1500-2300N / 2.5cm, and the gram weight is 450-850g / m 2 .

2. The weather-resistant exposed coating composite waterproof coiled material according to claim 1, wherein: In the modified material, the asphalt is 90# asphalt, and the softening point of the 90# asphalt is ≥46°C; and / or, In the modified material, the basicity of the polyaluminium chloride is 45-80%.

3. The weather-resistant exposed coating composite waterproof coiled material according to claim 1, wherein: In the exposed coating composite layer, the sodium oxide content in the glass fiber cloth is ≤1wt%.

4. The weather-resistant exposed coating composite waterproofing membrane according to any one of claims 1 to 3, wherein: In the exposed coating composite layer, the weather-resistant acrylic coating is formed by a weather-resistant acrylic paint, and based on the total weight of the weather-resistant acrylic paint, the weather-resistant acrylic paint contains: 25-35wt% of a weather-resistant acrylic emulsion, 24-40wt% of water, 0.01-0.5wt% of cellulose ether, 25-35wt% of talc, and 1-6wt% of titanium dioxide.

5. The weather-resistant exposed coating composite waterproofing membrane according to any one of claims 1 to 3, wherein: In the exposed coating composite layer, the content of the weather-resistant acrylic coating is 100-300 g relative to the square meter of the glass fiber cloth.

6. The weather-resistant exposed coating composite waterproofing membrane according to any one of claims 1 to 3, wherein: The reinforcement layer is formed of reactive sand having a weight average diameter of 0.25-0.7 mm; and / or, The isolation layer is a PET silicone oil film and / or a PE silicone oil film.

7. A method for preparing the weather-resistant exposed coating composite waterproof coiled material according to any one of claims 1 to 6, characterized in that: The method comprises the following steps: (1) applying a weather-resistant acrylic coating to one side of a glass fiber cloth to obtain an exposed coating composite layer containing a weather-resistant acrylic coating; the glass fiber cloth has a tensile breaking strength of 1500-2300 N / 2.5 cm and a gram weight of 450-850 g / m 2 ; (2) applying the material I forming the reinforcement layer to the surface of the weather-resistant acrylic coating of the exposed coating composite layer to obtain an intermediate I; (3) coating the modified material for forming the modified asphalt layer on the surface of the exposed coating composite layer of the intermediate I, and performing a molding process to obtain a molding material I containing the modified asphalt layer; Optionally, the method further comprises: bonding an isolation layer to the surface of the modified asphalt layer of the molding material I; In step (3), based on the total weight of the modified material, the modified material contains: 40-55wt% of asphalt, 0.5-2wt% of polyaluminium chloride, 5-10wt% of cyclohexane oil, 2-8wt% of SBS, 2-6wt% of SBR, 0.5-3wt% of tris(2,3-dichloropropyl) phosphate, 2-6wt% of SIS, 0.05-1wt% of 3-methylthiazolidine-2-thione, 8-15wt% of coumarone resin, and 20-30wt% of aluminium hydroxide.

8. The method according to claim 7, wherein: In step (1), the method further comprises: first drying the glass fiber cloth coated with the weather-resistant acrylic paint to obtain the exposed paint composite layer; and / or, In step (2), the method further comprises: subjecting the exposed coating composite layer coated with the material I to a drying treatment II to obtain the intermediate I.

9. The method according to claim 7, wherein: In step (3), the molding process includes: subjecting the intermediate I coated with the modified material to a constant thickness extrusion process.

10. The method according to any one of claims 7 to 9, wherein: The method further comprises: before carrying out the step (3), first preparing the modified material by a method comprising the following steps: S1: in the presence of an organic solvent, subjecting the asphalt, the polyaluminium chloride and the naphthenic oil to a first reaction to obtain a first product; S2: subjecting the first product to a second reaction with the SBS to obtain a second product; S3: performing a third reaction on the second product, the SBR, the tris(2,3-dichloropropyl) phosphate and the SIS to obtain a third product; S4: performing a fourth reaction on the third product, the 3-methylthiazolidine-2-thione and the coumarone resin to obtain a fourth product; S5: performing a fifth reaction on the fourth product and the aluminum hydroxide to obtain the modified material; Wherein, the reaction conditions of the first reaction, the second reaction, the third reaction, the fourth reaction and the fifth reaction each independently include: a reaction temperature of 160-185° C., and a reaction time of 60-130 min.

Citation Information

Patent Citations

  • SBS modified asphalt waterproof coiled material with enhancement layer

    CN105398103A

  • Preparation method of thermoplastic polyurethane modified asphalt waterproof coiled material

    CN109878190A

  • Self-adhesive polymer modified asphalt coiled material for buildings as well as preparation method of self-adhesive polymer modified asphalt coiled material

    CN108424730A

  • Exposed composite waterproof special polymer asphalt waterproof coiled material

    CN209454285U